Plan de comercialización para la Asociación de Producción Agropecuaria Mujeres Apícolas La Barranca parroquia Boyacá cantón Chone - Intriago Zambrano, Xiomara Elizabeth (2025)
The main objective of this research was to develop a marketing plan to strengthen the sales strategies of apicultural products from Asoproamuaba. A mixed-methods approach was employed, combining quantitative and qualitative methodologies to provide a comprehensive analysis of the association’s current situation. Surveys were used to collect numerical data on consumer behavior and market trends, while interviews offered deeper insights into perceptions and experiences. The research design incorporated descriptive, analytical, and field methods, supported by tools such as SWOT, PESTEL, and Porter’s Five Forces. A non-probabilistic convenience sampling method was applied, with a total of 270 participants. The study was carried out in phases: diagnosis, market analysis, and commercial proposal. The main findings indicate that Asoproamuaba faces significant challenges, such as informality in its commercial practices and the absence of administrative procedures. However, opportunities were also identified, including targeting young and female audiences and adjusting pricing to improve product accessibility. The study concludes that a well-structured marketing plan is essential to boost sales and ensure business sustainability, as the introduction of apicultural products into the local market represents a meaningful innovation in Boyacá parish in Chone canton. Despite challenges such as informality and limited market knowledge, the presence of a young and female consumer base provides fertile ground for strategies focused on organic products and effective promotions.